Generalization of Favard's and Berwald's Inequalities for Strongly Convex Functions - Khan, Muhammad Adil; Ullah, Syed Zaheer; Chu, Yuming (Communications in Mathematics and Applications, 2019)
In this paper, we give generalization of discrete weighted Favard's and Berwald's inequalities for strongly convex functions. The obtained results are the improvement and generalization of the earlier results.
Keywords: Majorization theorem; Strongly convex function; Favard's inequality; Berwald's inequality